2020
DOI: 10.1177/0007650320928969
|View full text |Cite
|
Sign up to set email alerts
|

CSR Communication, Corporate Reputation, and the Role of the News Media as an Agenda-Setter in the Digital Age

Abstract: By using social media, corporations can communicate about their corporate social responsibility (CSR) to the public without having to pass through the gatekeeping function of the news media. However, to what extent can corporations influence the public’s evaluation of their CSR activities with social media activities and if the legacy news media still act as the primary agenda setters when it comes to corporate reputation have not yet been thoroughly analyzed in a digitized media environment. This study addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 76 publications
2
57
0
3
Order By: Relevance
“…corporate websites) (Chapple and Moon, 2005), this study uses a non-corporate, providing an alternate view of CSR discourses. Second, while most previous research in the media coverage of CSR issues only focused on one country/region (Tam, 2015; Vogler and Eisenegger, 2020), this study included the samples from both developed and developing markets of CSR, showing a comparative view of CSR conceptualization in different societies with the influence from a variety of institutional factors. Third, the majority of previous studies used traditional content analysis with manual coding to handle a small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…corporate websites) (Chapple and Moon, 2005), this study uses a non-corporate, providing an alternate view of CSR discourses. Second, while most previous research in the media coverage of CSR issues only focused on one country/region (Tam, 2015; Vogler and Eisenegger, 2020), this study included the samples from both developed and developing markets of CSR, showing a comparative view of CSR conceptualization in different societies with the influence from a variety of institutional factors. Third, the majority of previous studies used traditional content analysis with manual coding to handle a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, Luo et al (2019) used a meta-analysis of agenda-setting and suggested that both the first-level and second-level agenda setting were equally powerful in influencing the public perception of the issues and their attributes. An increasing number of empirical studies have incorporated agenda-setting theory across a variety of media, including newspapers (Tam, 2015), online media (Roberts et al , 2002) and social media (Vogler and Eisenegger, 2020). Compared to other types of media, newspapers have stronger agenda-setting effects on shaping public perceptions (Luo et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Recientemente, se ha demostrado que la importancia y el tono de las noticias de RSE en los medios de comunicación tradicionales se relacionan positivamente con la reputación de una empresa, incluso si la noticia es negativa. Sin embargo, en redes sociales, no se ha demostrado la existencia de un vínculo claro entre las noticias de RSE de la empresa y su reputación (Vogler y Eisenegger, 2020). Por lo tanto, en la literatura previa se ha observado que el contenido generado por el usuario, las comunicaciones cara a cara y el poder de los medios tradicionales siguen siendo fuentes clave de reputación.…”
Section: Barreras Para De La Comunicación De La Responsabilidad Social Corporativaunclassified